Brachytherapy for benign fundus lesions. (August 2014) - Mehat, Manjit S; Jackson, Timothy L; Sagoo, Mandeep S
Abstract : Brachytherapy is the surgical placement of a radioactive source near a target lesion to allow local therapeutic delivery of radiation, in an effort to limit collateral damage to adjacent tissues by virtue of the restricted penetrative ability of the radioactive source. The eye is suited to brachytherapy since surgical access to the globe is relatively easy. For nearly 90 years, brachytherapy has been used to treat eye cancers such as retinoblastoma and uveal melanoma. Radiation risks may limit its appeal for treating benign fundus disorders, yet many of these lesions are sight threatening, and the risks of radiation can sometimes be mitigated. This article reviews the literature on the current use brachytherapy to manage benign fundus disorders. Broadly, this encompasses the treatment of benign but sight-threatening tumours, such as retinal capillary haemangiomas, vasoproliferative tumours and choroidal haemangiomas, and to attenuate angiogenesis, inflammatory and fibroblastic activity in neovascular age-related macular degeneration.